Financial technologies in money management, investments and financial services - Mykytyuk, Petro; Mykytyuk, Vitalii (Herald of Economics, 2025)
Introduction. The modern world is undergoing a transformation that encompasses all aspects of the economy, technology, and social life, and the financial sector is no exception. Financial technologies are becoming the driving force of this evolution, changing approaches to money management, investments, lending, and financial services in general. Thanks to the integration of artificial intelligence, blockchain, big data, and other innovations, financial services are becoming more accessible, personalized, and efficient, opening up new horizons for business and society. At the same time, this industry faces a number of challenges, such as the need to adapt to the regulatory environment, the growth of cyber threats, and ensuring financial inclusion for broad segments of the population. The development of financial technologies is taking on unique features in different regions of the world, from innovative platforms in the United States and Europe to revolutionary changes in financial services in Asia, Africa, and Ukraine. This multifaceted nature emphasizes the importance of global cooperation, technological progress, and a strategic approach to shaping the financial ecosystem of the future, which will be not only stable but also adapted to the needs of modern society.The purpose of the research is to deepen theoretical and methodological approaches to the management of financial services and innovative technologies aimed at optimizing, simplifying and reducing the cost of financial processes.Research methods. In the process of implementing the established goal of the scientific research, both general scientific and specific research methods were used, namely: generalization, induction and deduction, financial analysis and synthesis when establishing the influence of technological and innovative factors.The results. It was found that the future of financial technologies is promising. The main areas of development will be artificial intelligence, blockchain, open banking and decentralized finance (DeFi). It is expected that financial services will become even more personalized thanks to data analytics and customer behavior prediction. It was established that the development of supervisory (SupTech) and regulatory (RegTech) technologies will allow for more effective market monitoring, risk identification and transparency in the financial sector. Innovations in the field of cybersecurity will also become a priority, as users increasingly trust digital platforms with their financial data.The role of financial inclusion is identified, which will develop through the creation of accessible mobile platforms that provide services to people even in the most remote regions. Special emphasis will be placed on the development of financial literacy so that users can effectively use new tools. It is predicted that financial technologies will create new business models and stimulate their economic growth through innovation, which will have a significant impact not only in the financial sector, but also in people’s daily lives, changing the way they interact with their finances. The future of financial technologies is a digital transformation that will make financial services more accessible, efficient and secure for everyone.Prospects. Further research should be aimed at: creating and implementing a regulatory ‟sandbox” for rapid testing of innovations in the financial sector; increasing the level of financial literacy and involvement among the population and business; forming an educational base focused on implementing the concept of open banking; developing innovations in supervision and regulation technologies that ensure financial market stability, increase process efficiency, contribute to expanding the client base, as well as identifying and minimizing risks.